Teachers’ well-being from the social psychological perspective - Zawawi Zakaria; Yahya Don; Mohd Faiz Mohd Yaakob (International Journal of Evaluation and Research in Education (IJERE), 2021)
School is an important organizational unit in a country. School is also the foundation of every country’s education system. A harmonious working environment and a healthy relationship are very vital to ensure the high quality of teachers’ work. Issues in the workplace can lead to low performance, job dissatisfaction, loss of happiness, stress, and many other mental health issues. Teachers’ well-being is greatly influenced by comfortable, healthy, and happy conditions. Hence, this study aims to examine well-being among teachers in National Secondary Schools (SMK) and Government Funded Religious Schools (SABK) based on the quality of teachers’ working life such as psychological, social, political, and economic needs. This was quantitative research with a survey method using questionnaires as the instrument. The respondents of the study comprised 300 teachers in a district in Kelantan, Malaysia. The respondents were chosen based on a random sampling technique. The results of the study showed that the level of teachers’ well-being is high. There were no differences regarding the level of teachers’ well-being between SMK and SABK.